2001
DOI: 10.3109/10641950109152646
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Maternal Serum hCG in the Second Trimester Increases Prematurity Rate and Need for Neonatal Intensive Care in Primiparous Preeclamptic Pregnancies

Abstract: In primiparous preeclamptic pregnancies, an elevated maternal serum hCG concentration is a marker of early-onset and severe disease with significant maternal and perinatal morbidity. This finding, in turn, reinforces the association between elevated hCG concentrations and placental damage in early pregnancy. Elevated maternal serum hCG levels identify a subgroup of preeclamptic patients who deserve more intensive observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…However, similar to our findings for hCG alone, the results of other studies have suggested that high concentrations of hCG in the second and third trimester may be associated with increased risk of preeclampsia . A few studies have distinguished between term and preterm preeclampsia, and the authors have emphasized that the association of hCG may be stronger for preterm (or severe) than for term preeclampsia . Low concentrations of hCG in the first trimester have also been associated with increased risk in some studies but not in others .…”
Section: Discussionsupporting
confidence: 87%
“…However, similar to our findings for hCG alone, the results of other studies have suggested that high concentrations of hCG in the second and third trimester may be associated with increased risk of preeclampsia . A few studies have distinguished between term and preterm preeclampsia, and the authors have emphasized that the association of hCG may be stronger for preterm (or severe) than for term preeclampsia . Low concentrations of hCG in the first trimester have also been associated with increased risk in some studies but not in others .…”
Section: Discussionsupporting
confidence: 87%
“…Excluding articles that provided only studies evaluating human placental lactogen, placental alkaline phosphatase, or specific β1‐glycoprotein the findings of which were not generalizable owing to the low number of studies (File ), the literature search identified 29 articles eligible for inclusion in the meta‐regression analysis (Table and Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated free β‐hCG is presumed to result from abnormal placentation and placental hypoxia, a mechanism that is believed to be similar to low first‐trimester PAPP‐A levels . In the absence of chromosomal abnormality, elevated free β‐hCG has been reported to be linked with preterm delivery and IUGR in the second trimester . However, previous studies have failed to detect an association between elevated free β‐hCG and adverse pregnancy outcome in singleton pregnancies in the first trimester .…”
Section: Discussionmentioning
confidence: 99%